Trophallaxis in Lasius niger: a variable frequency and constant duration for three food types - Buffin, A; Mailleux, A.-C; Detrain, C; Deneubourg, J. L (Insectes sociaux, 2011)
While food recruitment and foraging have been the subject of many studies, the regulation of the food sharing behaviour remains poorly understood. In this study, we focused on trophallaxis (or mouth-to-mouth food exchange) within a group of worker ants as the first step in characterizing food sharing behaviours. In particular, we wanted to investigate the influence of the type of the food on trophallaxis. We studied three food types: a 1 M sucrose solution, a solution rich in proteins and a 1 M solution of melezitose, the latter being referred to as the ants' favourite sugar. Our results show that the type of the food influences the frequency of trophallaxis but not the duration of each food exchange. Indeed, the total number of trophallaxes differed with the type of food, whereas the duration of trophallaxis was similar regardless of the food exchanged. Furthermore, the probability of stopping an exchange per unit of time was constant and did not depend on the time the exchange had already lasted. This suggests that food distribution is principally regulated by the frequency of trophallaxis rather than the amount of food exchanged and brings new questions about the regulation of food flow between individuals.